Load modelling for steady-state and transient analysis of low voltage dc systems - Einarsson, Einar Pálmi; Wickbom, Bengt-Olof (My University, 2004)
In this thesis, common loads used in low-voltage residential and commercial power systems are investigated when supplied with dc. There steady-state and transient behavior is characterized, in order to build simple models suitable for computer simulation with PSCAD/EMTDC. Laboratory measurements were carried out on various loads that were categorized in resistive, rotating and electronic loads. From these measurements it was possible to characterize the steady-state behavior of loads. To indicate how much the load disturbs the network, the frequency spectrum was analyzed. To be able to analyze the transient response of the loads, a voltage reduction circuit was designed and constructed. The loads were subjected to several voltage steps in order to derive a simple dynamic model. Another objective of this work was to study the load sensitivity to voltage variations, in particular voltage dips, with dc supply and then compare the result to the same voltage variation in ac. The models developed in this thesis can be used for load flow, voltage dip and short circuit current calculations in a low voltage dc distribution system.
Keywords: Elkraftteknik; Electric power engineering